Heavy metal contamination in the Black River, Cape Town - Gilbert, Lucy Jane (Department of Environmental and Geographical Science, 2016)
Urban river sediments are often contaminated as a result of development and anthropocentric activity, and the Black River in Cape Town is a prime example of a river system suffering from unsustainable development. Methods of deter mining total and background concentrations of selected heavy metals were researched and utilized in the effort to quantify heavy metal concentrations derived from anthropogenic sources in the Black River . The findings were intended for use in the aim of producing sediment quality guidelines (SQG) for South Africa as described in the Water Research Commission Phase I Report; Developing Sediment Quality Guide lines (Gordon and Muller, 2010). The ability of the invasive Eichhornia crassipes (water hyacinth) to uptake and store heavy metals was also briefly investigated to identify its potential as a phyto - remediator in the Black River. Toxicity of the sediment was quantified using the consensus - based mechanistic approach (Gordon & Muller, 2010) whereby assuming that total concentration of a heavy metal is the critical factor in its hazardousness. Sediment samples were divided into grain size and measured by X - Ray Fluorescence and concentrations of the focus elements antimony, arsenic, cadmium, chromium, copper, nickel, lead, and zinc in the mud fraction were compared with Consensus Based Sediment Quality Guidelines (McDonald et al., 2002). Based on guide line exceedances, the most toxic sample was collected from anoxic sediment conditions at the point where the N2 Highway crosses the Black River. The succeeding high toxic ity risk locations were all within areas slightly downstream of a river convergence or within 50 m of one, specifically the Vygekraal, Jakkelsvlei, Esliekraal and Kromboom rivers. Exceedances were most common for chromium, copper, lead, nickel and zinc. The least toxic sample was collected 160 m downstream of the Athlone wastewater treatment works, with the one sample collected between these two points also holding relatively low toxicity risk. Concentrations of the selected analytes were also compared to results from a previous study conducted in 2002 on the Black River sediment (Haniff). The comparison suggested contamination has generally worsened in the past 13 years however due to potentially large analytical error from the differences in sample analyses in 2002 and in this investigation; the reliability of the comparative study is limited to general observation. The data implies that the Athlone wastewater treatment works was contributing to heavy metal concentrations in the sediment in 2002, but now in 2015 appears to improve sediment quality. The Water Research Commission Phase I report identifies four ways to assess sediment quality to produce SQG; one of which is to establish normal background concentrations. In this investigation, background concentrations of heavy metals from natural sediment input to the Black River was estimated using two methods, the first was by combining globally recognized average shale values (Turekian and Wedepohl, 1961; USGS, 2000) with results obtained from studies undertaken on virgin soils of the Black River catchment area (Soderberg, 2003; Herselman, 2007) to form what is referred to as Estimated Background Values (EBV). The second method was to measure element concentrations of weakly - acid rinsed and milled coarse grain fraction of the Black River sediments. This was to see whether concentrations of the coarse fraction reflect those of the EBV, and to establish whether this would be a feasible method of estimating background concentrations which takes into account the multiple inputs of natual sediment across the river catchment. It was concluded from the application of the t - test that the coarse grain fraction held similar concentrations to 19 major and trace elements of the EBV with 95% certainty, and were comparable for all the focus elements accept antimony and arsenic. The mud fraction heavy metal concentrations were then applied to three statistical indicators; the Pollution Load Index (PLI), the Geo - accumulation Index (I - Geo) and the Enrichment Factor (EF) in the objective to quantify anthropogenic input using both the EBV and coarse grain fraction results as reference values. All statistical indicators suggest the river is most enriched with cadmium, copper, lead and zinc, which most likely derive from roadside deposit/stormwater drainage and industries. The application of EBV to the statistical indicators revealed relatively little pollution enrichment, whereas the coarse grain results suggested much higher leve ls of pollution enrichment in the Black River. This disparity verifies the importance in selecting/obtaining suitable data sets as screening values for investigating heavy metal enrichment (Gałuszka & Migaszewski, 2012). It was concluded that the coarse grain fraction element concentrations would not be feasible for use as EBV in the case of the Black River. This is due to the large assumptions made whilst using this method, namely that the coarse grain fraction is assumed to derive from the same source as the mud fraction. Due to the known disturbances to natural sedimentation in the Black River, it is doubtful that the fractions come from the same source. Also given the relatively low heavy metal concentration in the coarse grain fraction, it is likely that the majority of the sand in the sediment of the Black River derives from the coastline. Heavy metal concentrations in the water hyacinth and sediments were applied to the Bio - accumulation Factor to identify the potential of the species as a phyto - remediating agent in the Black River. All four water hyacinth samples contained high concentrations of cadmium, and high concentrations of arsenic, nickel and antimony in three samples. Mercury was present (albeit at low concentrations) in three out of the four plant samples, yet was not detected in any of the 32 sediment samples, supporting the conclusions of Buta et al (2011) that the plant has a very strong affiliation to mercury, and that the element has a high affinity to bind with dissolved organic carbon and suspended sediment. The Bio - accumulation Factor revealed the phyto - remediation potential of the water hyacinth is high for antimony, arsenic, cadmium, mercury, lead and nickel. Water hyacinth could therefore be utilized more effectively (with the use of controlled growth) to remediate sediments indirectly by removing heavy metals from the water and preventing them settling into the sediment. Short - term fluctuations in heavy metal presence and kinetic components cannot be conservatively evaluated due to sediment disturbances, complexities within river system inputs and the ever changing environmental conditions. The findings are based on equilibrium status and the conditions at the time of sampling, and are limited to confinements of the reliability of data generated from sample collection, preparation methods and sample analysis. The distribution of metals in sediments of the Black River if not controlled by dredging is generally controlled by the association of heavy metals with very fine grained, organic - rich sediment. In addition, locations of high element enrichment reflect other river inputs which drain from various areas of the Cape Flats, with the most significant being the Esliekraal convergence. Conclusions from the investigation suggest the method of establishing background concentration from the coarse grain fraction could be applicable only to urban rivers which have seen few sedimentation disturbances and are relatively isolated from externa l sources away the local catchment. This method could reduce sampling costs and be used along with the application of other means available mentioned in the Water Research Commission Phase I report to create South African sediment quality guidelines.